1st Karl Schwarzschild Meeting on Gravitational Physics - Nicolini, Piero; Kaminski, Matthias; Mureika, Jonas; Bleicher, Marcus (Springer, 2016)
Part I The Life and Work of Karl Schwarzschild. -Karl Schwarzschild and Frankfurt (Frank Linhard) -- Part II Black Holes in Classical General Relativity, Numerical Relativity, Astrophysics, Cosmology and Alternative Theories of Gravity -- Black Hole Observations - towards the Event Horizon (Silke Britzen) -- Primordial Black Holes and Quantum Effects (B. J. Carr) -- There are no black holes - Pseudo-Complex General Relativity (Walter Greiner, Peter O. Hess, Mirko Schäfer, Thomas Schönenbach, and Gunther Caspar) -- Analytical solutions for geodesic equation in black hole spacetimes (Claus Lämmerzahl and Eva Hackmann) -- A physical derivation of the Kerr–Newman black hole solution (Reinhard Meinel) -- On the Black Holes in alternative theories of gravity: The case of non-linear massive gravity (Ivan Arraut) -- The Near-Horizon Limit (Jiří Daněk) -- Sourcing a Varying-Mass Black Hole in a Cosmological Background (Michele Fontanini, Daniel C. Guariento) -- Tidally Distorted Black Holes (Norman Gürlebeck) -- Self–completeness in Alternative Theories of Gravity (Maximiliano Isi, Jonas Mureika and Piero Nicolini) -- Gravitational collapse to black holes and more (Daniele Malafarina) -- Experimental Tests of Pseudo-Complex General Relativity (Thomas Schönenbach, Gunther Caspar, Peter O. Hess, Thomas Boller, Andreas Müller, Mirko Schäfer and Walter Greiner) -- Magnetic field amplification in hypermassive neutron stars via the magnetorotational instability (Daniel M. Siegel and Riccardo Ciolfi) -- Extracting information on the equation of state from binary neutron stars (Kentaro Takami, Luciano Rezzolla and Luca Baiotti) -- Part III Black Holes in Quantum Gravity and String Theory -- Higher Spin AdS / CFT correspondence & quantum gravity aspects of AdS/CFT (Martin Ammon) -- Black Holes in the Asymptotic Safety program (Alfio Bonanno) -- Quantum black holes and effective quantum gravity approaches (Xavier Calmet) -- The Black Hole Uncertainty Principle Correspondence (B. J. Carr) -- Scattering and unitarity methods in two dimensions (Valentina Forini, Lorenzo Bianchi and Ben Hoare) -- Gravity Duals to Non-Relativistic Quantum Field Theories (Andreas Karch and Stefan Janiszewski) -- A ‘regularized’ Schwarzschild solution (F.R. Klinkhamer) -- The Chemistry of Black Holes (Robert B. Mann) -- Black Holes in Supergravity (K. S. Stelle) -- Thermodynamic of Distorted Reissner-Nordström Black Holes in Five-dimensions (Shohreh Abdolrahimi) -- What is the Schwarzschild radius of a quantum mechanical particle? (Roberto Casadio) -- The Background Effective Average Action Approach to Quantum Gravity (Giulio D’Odorico, Alessandro Codello, and Carlo Pagani) -- Phase transitions of regular Schwarzschild-Anti-de Sitter black holes (Antonia Micol Frassino) -- Vector Fields and Kerr/CFT Correspondence (A. M. Ghezelbash) -- Black Holes in Non-relativistic Holography (Stefan Janiszewski) -- Black holes and running couplings: A comparison of two complementary approaches (Benjamin Koch, Carlos Contreras, Paola Rioseco, and Frank Saueressig) -- Quantum Harmonic Black Holes (Alessio Orlandi, Roberto Casadio) -- Holographic entanglement entropy of semi-local quantum liquids (Da-Wei Pang, Johanna Erdmenger, and Hansjörg Zeller) -- Quadratic Palatini gravity and stable black hole remnants (D. Rubiera-Garcia, Francisco S. N. Lobo, and Gonzalo J. Olmo) -- Kermions (Elizabeth Winstanley) -- Part IV Other Topics in Contemporary Gravitation -- Quantum Gravity and the Cosmological Constant Problem (J. W. Moffat) -- Emergent gravity and the cosmological constant (T. Padmanabhan) -- Tunnelling methods and Unruh-DeWitt detectors in curved spacetimes (Giovanni Acquaviva) -- Fermions on adS (Victor E. Ambrus, and Elizabeth Winstanley) -- Study on Rescaling Extrinsic Curvature in Gravitational Initial Data (Shan Bai and Niall ´O Murchadha) -- Massive gravities (Dennis D. Dietrich) -- Self Sustained Traversable Wormholes and Topology Change Induced by Gravity’s Rainbow (Remo Garattini) -- A general maximum entropy principle for self-gravitating perfect fluid (Sijie Gao) -- Dynamical holographic QCD model: resembling renormalization group from ultraviolet to infrared (Mei Huang and Danning Li) -- Modified Theories of Gravity with Nonminimal Coupling and the Faint Young Sun Paradox (Lorenzo Iorio) -- A Practical Look at Regge Calculus (Dimitri Marinelli and Giorgio Immirzi) -- Boundary States of the Potts Model on Random Planar Maps (Benjamin Niedner, Max Atkin and John Wheater) -- One-loop Effective Action in Quantum Gravitation (L. Rachwal, A. Codello, and R. Percacci) -- Heavy Probes in Strongly Coupled Plasmas With Chemical Potential (Andreas Samberg and Carlo Ewerz).
Keywords: Konferenzschrift; Gravitation; Schwarzes Loch